2004
DOI: 10.1098/rsbl.2003.0116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of male sterility on female remating in the Mediterranean fruitfly, Ceratitis capitata

Abstract: Mating-induced reductions in female receptivity are common in insects. These responses are of interest because of their utility in insect pest control. In addition, the control of receptivity is likely to be the subject of sexual conflict over remating frequency. We investigated the specif ic effect of male sterility on female receptivity in an important pest species, the Mediterranean fruitfly (medfly), in which sterile males are often used for population suppression. Sterile males performed less courtship, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 17 publications
0
74
0
5
Order By: Relevance
“…In C. capitata , virgin females live longer than non-virgin females (Chapman et al 1998), while female Drosophila that mate at high frequencies have shortened life spans (Fowler and Partridge 1989), largely due to the transfer of toxic Sfps (Chapman et al 1995). Both C. capitata and Drosophila females mate multiply (Markow 1996, Kraaijeveld and Chapman 2004) and it has been suggested that the reduced female longevity after mating is a side-effect of evolutionary conflict between the sexes (Chapman et al 1995). Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In C. capitata , virgin females live longer than non-virgin females (Chapman et al 1998), while female Drosophila that mate at high frequencies have shortened life spans (Fowler and Partridge 1989), largely due to the transfer of toxic Sfps (Chapman et al 1995). Both C. capitata and Drosophila females mate multiply (Markow 1996, Kraaijeveld and Chapman 2004) and it has been suggested that the reduced female longevity after mating is a side-effect of evolutionary conflict between the sexes (Chapman et al 1995). Ae.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect observation supporting this hypothesis is the lower percentage of Israeli females ovipositing (15% in September and 30% in AprilÐMay). In C. capitata females, the receptivity to a second mating has been reported to negatively correlate with female age (Chapman et al 1998, Kraaijeveld andChapman 2004). Moreover, mated males seem to be more efÞcient at inhibiting remating than virgin males (Vera et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…The C. capitata control programs based on SIT rely on the release of mass-reared, sterilized males into the target wild population, which should mate with wild females reducing the production of viable offspring (Knipling 1955). Kraaijeveld and Chapman (2004) showed that the low mating competitiveness of sterile males increases the probability of fertile matings. Although a high remating rate may exacerbate the problem of the low mating success of sterile males, the level/direction of paternity skew may add further uncertainties to be considered along with population variation in the overall mating behavior.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, the sperm of irradiated males have a lower fertilizing ability than those of normal males (Simmons 2001). In Mediterranean fruitfly, Ceratitis capitata, irradiated males mate less successfully with both virgin and nonvirgin females and are less effective at preventing or inhibiting female remating than normal males (Kraaijeveld and Chapman 2004).…”
Section: Introductionmentioning
confidence: 99%